Endoscopic pyloromyotomy for the treatment of severe and refractory gastroparesis: a pilot, randomised, sham-controlled trial - Martinek, Jan; Hustak, Rastislav; Mares, Jan; Vackova, Zuzana; Spicak, Julius; Kieslichova, Eva; Buncova, Marie; Pohl, Daniel; Amin, Sunil; Tack, Jan (Gut, 2022)
OBJECTIVE: Endoscopic pyloromyotomy (G-POEM) is a minimally invasive treatment option with promising uncontrolled outcome results in patients with gastroparesis. DESIGN: In this prospective randomised trial, we compared G-POEM with a sham procedure in patients with severe gastroparesis. The primary outcome was the proportion of patients with treatment success (defined as a decrease in the Gastroparesis Cardinal Symptom Index (GCSI) by at least 50%) at 6 months. Patients randomised to the sham group with persistent symptoms were offered cross-over G-POEM. RESULTS: The enrolment was stopped after the interim analysis by the Data and Safety Monitoring Board prior to reaching the planned sample of 86 patients. A total of 41 patients (17 diabetic, 13 postsurgical, 11 idiopathic; 46% male) were randomised (21 G-POEM, 20-sham). Treatment success rate was 71% (95% CI 50 to 86) after G-POEM versus 22% (8-47) after sham (p=0.005). Treatment success in patients with diabetic, postsurgical and idiopathic gastroparesis was 89% (95% CI 56 to 98), 50% (18-82) and 67% (30-90) after G-POEM; the corresponding rates in the sham group were 17% (3-57), 29% (7-67) and 20% (3-67).Median gastric retention at 4 hours decreased from 22% (95% CI 17 to 31) to 12% (5-22) after G-POEM and did not change after sham: 26% (18-39) versus 24% (11-35). Twelve patients crossed over to G-POEM with 9 of them (75%) achieving treatment success. CONCLUSION: In severe gastroparesis, G-POEM is superior to a sham procedure for improving both symptoms and gastric emptying 6 months after the procedure. These results are not entirely conclusive in patients with idiopathic and postsurgical aetiologies. TRIAL REGISTRATION NUMBER: NCT03356067; ClinicalTrials.gov.
Keywords: Pyloromyotomy; Female; Prospective Studies; vyprazdňování žaludku; gastroskopie; ženské pohlaví; výsledek terapie; mužské pohlaví; prospektivní studie; lidé; pyloromyotomie; gastroparéza; Gastric Emptying; Gastroscopy; Male; Treatment Outcome; Humans; Gastroparesis